A study to evaluate the knowledge of women about the prevention of carcinoma cervix by vaccination - Sultana, Meher; Shammi, Tahmina Khan; Akhter, Sabina; Nancy, Farhana Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer, characterized by malignant growth in the cervix uteri, often manifests with vaginal bleeding and can progress silently until reaching an advanced stage. It ranks as the most common cancer among women in numerous developing nations. The study aimed to evaluate the knowledge of the women about the prevention of carcinoma cervix by vaccination. Methods: This cross-sectional observational study was conducted at the outpatient department of obstetrics and gynecology, Dhaka medical college and hospital, Bangladesh from Jan 2020 to Dec 2021. In this study, 100 women attending the mentioned department, were interviewed with a view in mind to find out their knowledge level regarding the vaccination of cervical cancers. Data were analyzed by using MS office tools. Results: The study revealed a direct correlation between education level and awareness of HPV, underscoring a significant lack of knowledge about cervical cancer vaccination. It emphasizes the urgent need to educate individuals about the vaccine’s role in preventing cervical cancer. Education campaigns utilizing local media could effectively disseminate information. Conclusions: The unavailability and cost of the vaccine pose barriers to its accessibility. Integrating the vaccine program into existing expanded program on immunization (EPI) initiatives could be transformative for community health.